(untitled) (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This article sought to comparatively examine different types of signs in Reuters news agency photos from Peirce and Burgins perspectives. The research data are photos with social and cultural themes being selected from the Reuters news agency which depicted the Iranian customs, traditions and culture. The research is accomplished focusing on a variety of signs from Peirce and Burgins perspectives. This study attempted to answer these questions that In Reuters social photos which sign has the highest frequency, Can semiotic theories be applied for photo interpretation and does the semiotics study of Reuters social photos lead to the fact that photography has an arbitrary system The findings showed that 14 photos were consistent in terms of Burgin and Peirces perspectives, but for 16 photos, these two views were incompatible with each other. According to the fact that the data analyzed in this study were photos, all photos had an iconic relationship with their object (theme).Therefore, the iconic signs were 30 enjoying the highest frequency. The indexical signs had a frequency of 14 and the last belonged to symbolic signs with 10 cases. The findings also suggested that semiotic theories can be applied in photos interpretation. In addition, the semiotics in Reuters social photos made it clear that photography has an arbitrary system